Impact of Age on Female Fertility: A Cross-Sectional Analysis of Reproductive Outcomes, Hormonal Profile, and Body Mass Index - Uzlifat Khatak, Iffat Kehkashan, Bibi Sakina, Farah Saleem, Rafaqat Malik, Aneela Mumtaz, Sana Adil (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The age factor on female fertility has been found to be a strong determinant and reproductive potential is also on the decline with age. This decrease is connected with the loss of ovarian reserve, hormonal alterations, and the risk of adverse pregnancy outcomes. Objective: To assess the impact of age on female fertility by analyzing reproductive outcomes, hormonal profiles, and body mass index (BMI) among women of reproductive age. Methods: The study was carried out in Al Khidmat Hospital between January 2023 to June 2023 involving 218 women aged 18 to 45 years to seek fertility assessment. Participants were stratified into four age groups (≤25, 26–30, 31–35, and 36–45 years). BMI, hormonal profile (FSH, AMH) and reproductive outcomes (clinical pregnancy, live birth, miscarriage) data were collected. The SPSS version 26 was used to conduct statistical analysis, which involved ANOVA and t-tests. A p-value ≤0.05 was considered significant. Results: The mean age of participants was 29.8 ± 6.2 years. A significant decline in fertility outcomes was observed with increasing age. Clinical pregnancy and live birth rates were highest in younger women (≤25 years) and decreased progressively in older age groups (p=0.002 and p=0.001, respectively). Miscarriage rates increased significantly with age (p<0.001). Hormonal analysis showed a decline in AMH levels and an increase in FSH levels with advancing age (p<0.001). Higher BMI was also significantly associated with adverse fertility outcomes. Conclusion: Advancing age significantly reduces female fertility, with declining ovarian reserve and increasing miscarriage risk. Early fertility assessment and lifestyle interventions are essential to improve reproductive outcomes. Keywords: Female fertility, Age, AMH, FSH, BMI, Miscarriage, Live birth